Stevens-Johnson syndrome is an immune catastrophe - E.K. Isaeva (LCC «Medicine-Inform», 2019)
Stevens-Johnson syndrome is an immune catastrophe S.I. Bardenikova1, O.S. Pentkovskaya2, E.K. Isaeva2 1 Moscow State University of Medicine and Dentistry named after A.I. Evdokimov, Moscow,  Russian Federation 2 Children's City Clinical Hospital of St. Vladimir, Moscow, Russian Federation Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are rare acute life-threatening skin and mucosal disorders provoked in children mainly by infections and/or medications. According to the modern concept, SJS is a minor variant of TEN characterized by a total area of epidermal detachment less than 10% of the body surface area. However, a patient may present with deep mucosal lesions of at least two organs, e.g., larynx, trachea, bronchi, gastrointestinal tract, bladder or urethra. TEN is characterized by massive epidermolysis which involves more than 30% of the body surface area. Polypragmasia make difficulties for trigger identification while the severity depends on trigger withdrawal and elimination. This disorder is uncommon in paediatrics. Diagnosis is verified mainly by clinical manifestations. SJS debut is similar to acute respiratory infections and rash infections. Late diagnosis is associated with poor outcomes. There are no uniform treatment algorithms, individual treatment choice is required. Clinical case demonstrates that early diagnosis and treatment are vital. Key words: Stevens-Johnson syndrome, toxic epidermal necrolysis, epidermolysis, life-threatening condition, apoptosis, children, trigger, mask, treatment algorithm. For citation: Bardenikova S.I., Pentkovskaya O.S., Isaeva E.K. Stevens-Johnson syndrome is an immune catastrophe. Russian Journal of Woman and Child Health. 2019;2(1):66-72.